Pengaruh Current Ratio (CR), Earning Per Share (EPS), Price Earning Ratio (Per) Dan Debt To Asset Ratio (DAR) Terhadap Harga Saham Pada PT. Gudang Garam TBK Periode 2012-2021 - Cellia, Cindy; Sudaryo, Yoyo; Herlinawati, Erna (Fakultas Ekonomi Universitas Gresik, 2023)
This study aims to examine Current Ratio (CR), Earning Per Share (EPS), Price Earning Ratio (PER) and Debt to Asset Ratio (DAR) to stock prices at PT. Gudang Garam Tbk. The research sample was selected using a purposive sampling technique and resulted in one company with the 2012-2021 research period. This study uses a quantitative approach with secondary data through the documentation method. Data was obtained from the company's official website, the length of the Indonesian Stock Exchange (IDX), and other supporting periods. This study uses descriptive analysis and verification analysis using Microsoft Excel and SPSS 25. The results of this study indicate that Earning Per Share (EPS) and Price Earning Ratio (PER) significantly affect stock price. In contrast, Current Ratio (CR) and Debt to Asset Ratio (DAR) has no significant effect on stock price